Sociological analysis of the cause of psychological fatigue and burnout in professional athletes - Xie, B. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Owing to severe psychological strain and mental stress on athletes during training and competition, it is very common for athletes to suffer psychological fatigue and burnout. Burnout is one of the main factors influencing their training and competition performance. Bio-psychological sociology modelling has been used in research since 1990 to analyze the cause of fatigue and burnout. The most widely acknowledged description of athlete burnout stems from Smith`s (1986) cognitive-affective model of stress that suggests burnout is one consequence of recognizing and evaluating the environment including any factors which may influence the athlete. Training satisfaction as a cognitive evaluation is the emotional reaction which is formed through evaluating the training process and those factors which are related to training such as team organization, coaching and teammates. According to Smith`s analysis, there is a close relationship between the burnout of an athlete and training satisfaction. Therefore, by exploring the relationship between burnout and satisfaction, this study discusses the causes of fatigue and burnout of athletes in Chinese team sports. The results provide suggestions and methods to help athletes and coaches prevent these undesirable traits, keeping athletes in a good competitive state of mind. Methods 206 athletes participated and completed 2 questionnaires. The first was the athletes training satisfaction questionnaire (Xie (2007), consisting of 44 items. There are 4 dimensions: satisfaction with sport organization, satisfaction with oneself, satisfaction with the coach and satisfaction with team mates and each dimension has 2 or 3 components. The second questionnaire (Ning, 2003) consisted of 32 items with 2 dimensions: stress and resume. The stress dimension is composed of 4 indexes evaluating athlete fatigue and burnout. The resume dimension also contains 4 components evaluating the athlete`s preparedness for competition. Canonical Correlation Analysis was used to analyse the correlation between each training satisfaction dimension and stress and resume respectively. Results Satisfaction with an athletes` self correlates with stress and resume more strongly than satisfaction with coaches and team organization. Among all the ingredients of training satisfaction, daily administration of team organization, confidence and devotion, growing and progress of an athlete, democratic behaviour and individual concern of coaches show a significant relationship (R > 0.05) with an athlete`s psychological fatigue and burnout, self-efficiency, self-adjustment and physique resume. These results imply that besides satisfaction with oneself, the management of the team and instruction from the coach are other external factors contributing to an athlete`s psychological fatigue and burnout. Discussion From a sociological perspective, the study discusses the cause of athlete fatigue and burnout in Chinese professional athletes. The training system in China should be constantly improved with scientific and humanistic management approaches being established for sports teams. In addition, coaches should give more consideration and concern to athletes, aiming to improve their own instructional skills. With the adoption of these suggestions, teams may help to prevent fatigue and burnout.